2010
DOI: 10.1016/j.tecto.2009.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for ancient lithospheric deformation in the East European Craton based on mantle seismic anisotropy and crustal magnetics

Abstract: International audienceWe present new shear-wave splitting measurements performed at 16 stations on the East European Craton, and discuss their implications in terms of upper-mantle anisotropy for this geophysically poorly-known region. Previous investigations of mantle anisotropy in Central Europe have shown fast directions aligning smoothly with the craton's margin and various suggestions have been proposed to explain their origin such as asthenospheric flow or lithospheric frozen-in deformation.;Here, we aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 111 publications
1
17
0
Order By: Relevance
“…As noted above, various explanations for observed crustal anisotropy have been suggested. Proposed models for anisotropy include alignment of microcracks [ Crampin et al , 1984; Kaneshima et al , 1988], preferred mineral alignment [ Christensen and Mooney , 1995], fossil anisotropy created during the last tectonic event [ Wüstefeld et al , 2010; Bastow et al , 2011], plate motion [ Bokelmann and Wüstefeld , 2009], stress direction [ Crampin , 1981] and fabrics defined by geologic structures [ Lin et al , 2011]. In this section, we explore some of these models to help determine the origin of the anisotropic fabric in our data.…”
Section: Discussionmentioning
confidence: 99%
“…As noted above, various explanations for observed crustal anisotropy have been suggested. Proposed models for anisotropy include alignment of microcracks [ Crampin et al , 1984; Kaneshima et al , 1988], preferred mineral alignment [ Christensen and Mooney , 1995], fossil anisotropy created during the last tectonic event [ Wüstefeld et al , 2010; Bastow et al , 2011], plate motion [ Bokelmann and Wüstefeld , 2009], stress direction [ Crampin , 1981] and fabrics defined by geologic structures [ Lin et al , 2011]. In this section, we explore some of these models to help determine the origin of the anisotropic fabric in our data.…”
Section: Discussionmentioning
confidence: 99%
“…Plomerova et al (2007) interpret the broad low-velocity anomaly beneath the Eger Rift as an upwelling of the LAB. The authors also find different orientations of seismic anisotropy corresponding to the major tectonic units in the Bohemian Massif (i.e., Saxothuringian, Moldanubian and Tepla-Barrandian), while the studies of shear-wave splitting (e.g., Wüstefeld et al, 2010;Vecsey et al, 2013;Sroda et al, 2014) show that anisotropy in the I. Janutyte et al: Upper mantle structure around the Trans-European Suture Zone Bohemian Massif is higher compared to the anisotropy observed in the TESZ and even smaller, but still noticeable, for the EEC (Plomerova et al, 2008). Jones et al (2010) performed a comparison between the delineation of the LAB for Europe based on seismological and electromagnetic observations, and concluded that the LAB, as an impedance contrast from receiver functions, as a seismic anisotropy change and as an increase in conductivity from magnetotellurics, are consistent with the deeper LAB beneath the EEC and the shallower LAB beneath central Europe, which coincides with conclusions by Korja (2007), who made a review of previous studies of magnetotelluric imaging of the European lithosphere.…”
Section: Review Of Previous Studiesmentioning
confidence: 98%
“…Assumpção et al (2011) explain variations in average splitting parameters beneath the South America cratons by local deflections of the sub-lithospheric flow due to lithosphere thickness variations. On the other hand, Barruol et al (2008) and Wüstefeld et al (2010) found several arguments supporting frozen lithospheric anisotropy in cratonic areas. Mareschal and Jaupert (2006) estimate temperatures at 150km depth during the Archean only 150 K higher that present, implying the lithosphere remains sufficiently cold and strong to preserve Archean fabrics.…”
Section: P R O T E R O Z O I Cmentioning
confidence: 99%
“…Both the sharpness of boundaries of the domains mapped according to changes of the anisotropic body-wave parameters, and the correlation between the mantle boundaries and dominant tectonic sutures on the surface, justify us to associate the observed anisotropy with fossil preferred orientation of olivine in the mantle lithosphere. Generally accepted weak asthenosphere flow beneath cratons could hardly produce such abrupt changes observed beneath the shield (Vecsey et al, 2007;Eken et al, 2010;Wüstefeld et al, 2010). For the first simple estimates of the lithosphere domain fabrics, we invert the P-spheres for the symmetry axes orientation and calculate synthetic shear-wave splitting parameters for a comparison with the observed ones (Fig.…”
Section: Modelling the Mantle Lithosphere Domains Delimited By Body-wmentioning
confidence: 99%